2020
DOI: 10.7759/cureus.12022
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline-Induced Acute Eosinophilic Pneumonia

Abstract: Acute eosinophilic pneumonia (AEP) is a rare but severe respiratory syndrome characterized by fever, hypoxemic respiratory failure, diffuse pulmonary infiltrates, and pulmonary eosinophilia. The most common cause of AEP is idiopathic, but it can be associated with antidepressant medications like sertraline.A 76-year-old female presented to our ED with acute hypoxemic respiratory failure. She had no history of smoking or prior lung disease. She did not improve after treatment with broad spectrum antibiotics so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The presence of these conditions are secondary to prescriptions for antidepressants including fluoxetine, amitriptyline, and desipramine; anticonvulsants including phenytoin, valproate, lamotrigine, and carbamazepine; antibiotics including penicillins, cephalosporins, and quinolones; nonsteroidal anti-inflammatory drugs including naproxen, diclofenac, and ibuprofen; antihypertensive agents including angiotensin-converting enzyme inhibitors, b-blockers, and hydrochlorothiazide; and sulfasalazine and allopurinol. [2][3][4] In addition, several studies have reported eosinophilia or hypereosinophilia related to psychotropic drugs such as paroxetine, sertraline, venlafaxine, duloxetine, 5 lithium, olanzapine, 3 clozapine, 4 quetiapine, risperidone, 6 ziprasidone, 7 and aripiprazole. 8 However, mirtazapine has not yet been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these conditions are secondary to prescriptions for antidepressants including fluoxetine, amitriptyline, and desipramine; anticonvulsants including phenytoin, valproate, lamotrigine, and carbamazepine; antibiotics including penicillins, cephalosporins, and quinolones; nonsteroidal anti-inflammatory drugs including naproxen, diclofenac, and ibuprofen; antihypertensive agents including angiotensin-converting enzyme inhibitors, b-blockers, and hydrochlorothiazide; and sulfasalazine and allopurinol. [2][3][4] In addition, several studies have reported eosinophilia or hypereosinophilia related to psychotropic drugs such as paroxetine, sertraline, venlafaxine, duloxetine, 5 lithium, olanzapine, 3 clozapine, 4 quetiapine, risperidone, 6 ziprasidone, 7 and aripiprazole. 8 However, mirtazapine has not yet been reported.…”
mentioning
confidence: 99%
“…5 In addition, serotonin also has a chemoattractant factor for eosinophils through expressed 5-HT 2A receptor, then mediates eosinophil recruitment, and leads to an inflammatory reaction and hypersensitivity. 5,10 Interestingly, the selective activation of 5-HT 2A receptors has potent antiinflammatory activity in animal models, preventing the development of eosinophil recruitment and migration by reducing IL-5 and granulocyte-macrophage colony-stimulating factor levels and monocyte chemoattractant protein-1 secretion. 11 Mirtazapine may be relevant because of its antagonistic effects on 5-HT 2A receptors.…”
mentioning
confidence: 99%